Design and Analysis of a Broadband Microwave Amplifier - Obinna Okoyeigbo; Augustus E Ibhaze; Ayobami Olajube; Olamilekan Shobayo; Tobiloba Somefun; Onyinyechi Steve-Essi (IAES Indonesian Section, 2021)
This paper presents the procedures involved in the design and analysis of a microstrip broadband microwave amplifier. For system design, simulation, optimization and analysis, a Computer Aided Design (CAD) tool know as Agilent Advanced Design System (ADS) was employed. The amplifier device- FLC317MG-4 FET, was tested for stability, and was observed to be unconditionally stable between 2 to 6 GHz frequency band. Two possible ideal matching circuits were investigated to identify the best matching circuit with the maximum transducer power gain. It was observed that the quarter-wave transformer with parallel open circuit stub, gave a high gain at a wider range of frequency (larger bandwidth/ broadband), than the other matching circuit. Hence, it was employed for the broadband amplifier design using microstrips, and achieved a maximum flat gain of about 9.8 dB to 10.118 dB, at a bandwidth of 3.5 to 4.5 GHz.